Narrating 1Malaysia: nationalism and patriotism in Malaysian literature written in English - Mohd Ramli, Aimillia (2010)
Malaysian literature in English in the 1960s was a product of early Malaysian writers’ endeavour to spearhead a literary tradition of writings that promoted a national identity amongst the diverse races living the country. This task, however, was generally undertaken by those who were more inclined to write about the issues and interests of their own communities rather than those of others living in the country. In the last twenty years, however, there have emerged a number of fictional writings that depict not only the country’s multiracial context but also imply the existence of a sense of national consciousness and patriotic feelings amongst Malaysians. These writings, this paper suggests, veer away from the communal interest of individual ethnic groups by exploring interracial relationships, returning to historical junctures, assessing the effect of globalization and, finally, conjuring alternative cultural paradigms with the single aim of unifying Malaysians and embedding them with the nationalistic spirit of 1Malaysia.